Estimating Truck Traffic Generated from Well Developments on Low-Volume Roads. Issue 10 (October 2020) - Tsapakis, Ioannis
Recent advances in horizontal drilling and hydraulic fracturing technologies have allowed producers to extract oil and gas from thin reservoirs that may not be economically viable through vertical drilling. While the new hydraulic fracturing technologies have resulted in substantial economic benefits for the state of Texas, they tend to generate high volumes of truck traffic that diversely affect the transportation system. Many of the affected roads were designed and built several decades ago to meet low traffic demand levels and not heavy repetitive truck loads. The goal of this study is to enhance state agencies' ability to determine the truck traffic associated with fracking in existing and new wells based on several well characteristics. This paper explores spatio-temporal trends in hydraulic fracturing in Texas and develops a methodology that agencies can use to estimate the amount of water and the number of trucks needed to frack and fully develop a well. The analysis revealed that fracking horizontal wells generates eight times more water and, therefore, truck traffic than vertical wells. The relationship between water volume versus well length is non-linear. The length of laterals has a very strong correlation with frack water (0.818) and sand (0.763), while the vertical well depth has a weak to negligible relationship with fracking materials. The two prediction models presented in the paper produced statistically similar results with average errors of less than 20%. The paper explains how the predicted water volumes can be converted into the number of trucks needed to frack and fully develop a well.